Plant diversity alters the representation of motifs in food webs - Darren P. Giling (Nature Portfolio, 2019)
Plant diversity affects ecosystem function in myriad ways, but the effect on food webs has received less investigation. Here, the authors use high-resolution food web data from a grassland diversity experiment to show that apparent and exploitative competition motifs increase with plant diversity.